Language and Social Change in Central Europe - PATRICK STEVENSON, JENNY CARL (Edinburgh University Press, 2010)
Why Switzerland? Jonathan Steinberg poses this beguilingly simple and provocative question in the title of his popular social history of the small alpine nation (Steinberg 1976, 1996). The choice of title was justifi ed by the book’s project, which was to explain two – later three – key questions: ‘why a place as idiosyncratic as Switzerland existed, and why non- Swiss should care’ (the third question, added in the second edition, was ‘why Switzerland should continue to exist’; Steinberg 1996: xi). Curiously though, in his preliminary discussion of these issues, the author places Switzerland ‘at the geographical centre of Europe’ (xii). While a case can be made for including the country in some conception of ‘central Europe’, the geographical centre of the continent surely lies signifi cantly further east – although, as Stanisław Mucha’s idiosyncratic search for this mythical place in the documentary fi lm Die Mitte (2004) shows, there are many competing locations that lay claim to the title (Stevenson and Carl 2009: 1). We raise these questions here because we were asked – and asked ourselves – similar questions in the course of the research on which this book is based. Why write about such a contentious and ill- defi ned space as central Europe? Why focus on the German language and its speakers? And why should anyone else care? We are, respectively, a British sociolinguist specialising in language ideologies and the politics of language in Germany, and a German social scientist with expertise in discourses on national and regional identity in the UK, so in exploring relationships between language and social change in what we should perhaps more properly call eastern central Europe we have both moved outside our familiar terrains.1 However, like Steinberg the historian of modern Europe specialising in Germany and Italy, we have taken our theoretical and methodological apparatus with us on our journey off - piste, not in the mistaken or deluded belief that we could travel virgin territory but in the hope of bringing a fresh perspective on what is indeed well- trodden ground. We are, for example, well aware of Tomasz Kamusella’s monumental and magisterial history of the politics of language and nationalism in modern central Europe (2008) and of the comprehensive survey of German linguistic minorities in this region provided by Eichinger et al. (2008), authoritative and perhaps defi nitive recent additions to two of the fi elds into which we are venturing here. However, we hope that our approach will complement such studies by drawing on diff erent disciplinary traditions and by telling a story that will reach both experts in the area and those whose interests lie elsewhere. In place of a more conventional introduction, therefore, we would like to devote these opening pages to a brief account of our own motivation in conducting this study and of what we hope to achieve.